Evolution of structure and local magnetic fields during crystallization of HITPERM glassy alloys studied by in situ diffraction and nuclear forward scattering of synchrotron radiation. Issue 42 (27th April 2015) - Miglierini, Marcel; Pavlovič, Márius; Procházka, Vít; Hatala, Tomáš; Schumacher, Gerhard; Rüffer, Rudolf
Abstract : In situ transformation of local structure and hyperfine interactions are simultaneously followed in real time during temperature annealing of metallic glasses. Abstract : Evolution of structure and local magnetic fields in (Fe1− x Co x )76 Mo8 Cu1 B15 (HITPERM) metallic glass ribbons with various amounts of Co ( x = 0, 0.25, 0.5) were studied in situ using diffraction and nuclear forward scattering of synchrotron radiation. It was found that crystallization of all three glasses proceeds in two stages. In the first stage, bcc (Fe, Co) nanocrystals are formed, while in the second stage additional crystalline phases evolve. For all three glasses, the crystallization temperatures at the wheel side were found to be lower than at the air side of the ribbon. The crystallization temperatures were found to decrease with increasing Co content. The lattice parameters of the bcc nanocrystals decrease up to about 550 °C and then increase pointing to squeezing Mo atoms out of the nanograins or to interface effects between the nanocrystals and the glassy matrix. Nuclear forward scattering enabled separate evaluation of the contributions that stem from structurally different regions within the investigated samples including the newly formed nanocrystals and the residual amorphous matrix. Even minor Co content ( x = 0.25) has a substantial effect not only upon the magnetic behaviour of the alloy but also upon its structure. Making use of hyperfine magnetic fields, it was possible to unveil structurally diverse positions of Fe atoms that reside in a nanocrystalline lattice with different numbers of Co nearest neighbours.